2003
DOI: 10.1177/104990910302000113
|View full text |Cite
|
Sign up to set email alerts
|

Opioids, respiratory function, and dyspnea

Abstract: Dyspnea, the sensation of difficult breathing, is a common debilitating symptom in advanced cancer and chronic progressive cardiopulmonary disease. Primary treatment is correction of the underlying etiology. In incurable illness wherein the cause is irreversible and the goal is palliation, opioids are the drugs of choice for symptomatic relief. This article reviews current knowledge in the pathophysiology of dyspnea, proposed opioid mechanism of action, and evidence of efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 41 publications
0
20
0
3
Order By: Relevance
“…Chronic ventilatory failure appears neither common nor clinically significant in advanced cancer patients who are pain-free on stable doses of opioids even in the presence of pre-existing respiratory disease [50]. In vitro studies have shown a respiratory depressant effect of opioids, which have led to cautious and sometimes inadequate low use by clinicians, although clinical experience supports efficacy and safety when doses are adjusted properly [49].…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Chronic ventilatory failure appears neither common nor clinically significant in advanced cancer patients who are pain-free on stable doses of opioids even in the presence of pre-existing respiratory disease [50]. In vitro studies have shown a respiratory depressant effect of opioids, which have led to cautious and sometimes inadequate low use by clinicians, although clinical experience supports efficacy and safety when doses are adjusted properly [49].…”
Section: Resultsmentioning
confidence: 98%
“…The exact mechanism of this depressant effect remains unclear and might be due to reduction in the sensitivity and responsiveness of the medullary respiratory centers to hypoxia and hypercapnia [48]. Opioids reduce minute ventilation by slowing the respiratory rate and decreasing tidal volume [49]. Students should be taught that there is no evidence for respiratory depression when carefully using opioids to manage dyspnea related symptoms, and, quite the contrary, are the golden standard drugs in managing acute dyspnea in palliative care patients.…”
Section: Resultsmentioning
confidence: 98%
“…Three recent reviews by different authors support the use of oral or parenteral (but not nebulized) opioids in the palliation of dyspnea even in patients with severe underlying lung disease. [87][88][89] Opioids also appear to relieve breathlessness in stable severe congestive heart failure (CHF) but showed no benefit in stable severe chronic obstructive pulmonary disease (COPD) or interstitial lung disease. 90,91 Although they are widely used, there is limited objective evidence for the benefit of benzodiazepines in the palliation of breathlessness.…”
Section: Respiratory Changesmentioning
confidence: 99%
“…Azonban a gyógyíthatatlan krónikus betegségek terminális stádiumában előállhat az az állapot, amikor minden lehetséges oki kezelés ellenére a fulladás továbbra is fennáll, a fulladás oka irreverzibilis, vagy specifi kus oki kezelésre nincs mód. Ilyenkor a beteg lég-szomjérzését opiátok adásával csökkenthetjük, illetve a fulladáshoz társult nagyfokú szorongást benzodiazepinekkel mérsékelhetjük [20].…”
Section: Légszomjunclassified